Fa’āliyah Wasāil al-Sam’iyyah al-Başariyah Yutub fī Tarqiyah Mahārah Istimā’ al-Lugah al-‘Arabiyah Ladā Țulāb al-Şaf al-Sābi’ fī Madrasah al-Mutawassiṭah al-Islamiyah al-Hukūmiyah, Semarang - Aida Lutfiyah; Dewi Rusliyani (KURAS Institute, 2024)
Teaching media play an important role in educational activities, including audio-visual media. One audio-visual that is very popular among different groups is YouTube.This research aims to determine the effectiveness of using YouTube video-based audiovisual media in improving the listening skills of Arabic for seventh-grade students at Islamic Middle School, Semarang. The research method used is a quantitative method with a survey design. The research instrument uses questionnaires and documentation. The research sample consisted of 30 class VII students at MTs N Semarang, based on Frangkel and Waalen's references.The questionnaire used in this research consists of 20 questions with a Likert scale to measure students' perceptions of the effectiveness of using YouTube video-based audio-visual media in improving their Arabic Listening Skills. The data obtained were analyzed using a one-way ANOVA test to determine the significant effect of using YouTube video-based audiovisual media on increasing students' Arabic listening skills.The criteria for ANOVA testing are if the significance value (sig.) > 0.05 then Ho is accepted. If the significance value (sig.) < 0.05 then Ho is rejected. The results of the ANOVA test show that the significance value is 0.009 < 0.05 and Ho is rejected, so it can be concluded that there is a significant influence of YouTube audiovisual media on increasing students' Arabic Listening Skills.This research shows that audiovisual media based on YouTube videos can be an effective tool for improving students' Arabic Listening Skills. The recommendation from this research is that educators make more use of this media in the learning process to create a more interesting and interactive learning atmosphere.